Assortative mating based on cooperativeness and generosity. (3rd March 2014) - Tognetti, A.; Berticat, C.; Raymond, M.; Faurie, C.
Abstract Cooperative behaviour and generosity towards nonkin represent costly and risky behaviour that could be used as a signal of mate quality. Therefore, cooperative traits could serve as criteria in mate choice, leading to assortative mating for those traits. There is evidence of similarity in couples for altruistic traits. However, the literature is based on self‐reports and does not provide conclusive proof of either a convergence across time or mating preferences. Here, we report a field experiment, conducted in rural villages in Senegal, showing that husbands and wives are similar with respect to their contributions to a public good and their charity donations. Further analyses suggest that this similarity is due to initial assortment rather than convergence of phenotypes.